Biological functions of extracellular vesicle double C2-like domain beta in cervical cancer - Sangavi Eswaran; Samatha Bhat; Dinesh Upadhya; Roshan Mascarenhas; Shama Prasada Kabekkodu (Scientific Reports)
Abstract Double C-2 Like Domain Beta (DOC2B) located at 17q13.3 prevents metastasis by senescence induction and epithelial to mesenchymal transition inhibition in cervical cancer (CC). The extracellular vesicle (EV) mediated trafficking of DOC2B and its impact on tumor suppressive activity are not investigated in CC. Using a retroviral method, we first ectopically expressed DOC2B in SiHa, which do not normally express DOC2B. DOC2B-SiHa and vector-SiHa EVs were co-incubated separately with recipient cell and subjected to various cellular and biochemical experiments. For the first time, we demonstrated that DOC2B localizes to EVs, and its transfer to EV may require intracellular calcium. Co-culture of SiHa and HeLa cells with DOC2B-SiHa derived EVs induced morphological changes and suppressed their growth and migration, possibly by induction of G0/G1 to S phase arrest and anoikis. DOC2B-SiHa EVs elevated intracellular reactive oxygen species (ROS) and calcium levels and promoted lipid droplet accumulation and lipid peroxidation rate in recipient cells. DOC2B-SiHa EVs reduced active AKT1 and ERK1/2 levels and EMT marker expression and enhanced cellular senescence and cytotoxic effects of cisplatin. Re-expression of DOC2B significantly altered the global metabolite profile of EVs.  Finally, we demonstrated that intracellular calcium chelation significantly reduces DOC2B localization to EVs and impacts its tumor-suppressive properties. Altogether, EV-mediated DOC2B transfer may reduce the aggressive behavior of CC cells.